Olfactory receptor 78 modulates renin but not baseline blood pressure. Issue 18 (21st September 2021) - Poll, Brian G.; Xu, Jiaojiao; Gupta, Kunal; Shubitowski, Tyler B.; Pluznick, Jennifer L.
Abstract: Olfactory receptor 78 (Olfr78) is a G protein‐coupled receptor (GPCR) that is expressed in the juxtaglomerular apparatus (JGA) of the kidney as well as the peripheral vasculature, and is activated by gut microbial metabolites. We previously reported that Olfr78 plays a role in renin secretion in isolated glomeruli, and that Olfr78 knockout (KO) mice have lower plasma renin activity. We also noted that in anesthetized mice, Olfr78KO appeared to be hypotensive. In this study, we used radiotelemetry to determine the role of Olfr78 in chronic blood pressure regulation. We found that the blood pressure of Olfr78KO mice is not significantly different than that of their WT counterparts at baseline, or on high‐ or low‐salt diets. However, Olfr78KO mice have depressed heart rates on high‐salt diets. We also report that Olfr78KO mice have lower renin protein levels associated with glomeruli. Finally, we developed a mouse where Olfr78 was selectively knocked out in the JGA, which phenocopied the lower renin association findings. In sum, these experiments suggest that Olfr78 modulates renin, but does not play an active role in blood pressure regulation at baseline, and is more likely activated by high levels of short chain fatty acids or hypotensive events. This study provides important context to our knowledge of Olfr78 in BP regulation. Abstract : Olfactory receptor 78 (Olfr78) is a GPCR expressed in the kidney and peripheral vasculature which is activated by gut microbial metabolites. Using radiotelemetry, we determined that Olfr78KO mice do not significantly differ from their WT counterparts with regards to baseline blood pressure. However, we report that Olfr78KO mice have lower renin protein levels associated with glomeruli by immunofluorescence. These experiments suggest that Olfr78 status modulates renin, but does not play an active role in blood pressure regulation at baseline.